2018
DOI: 10.5817/cp2018-1-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between online gaming motivation, self-concept clarity and tendency toward problematic gaming

Abstract: The aim of this study was to explore the relationship between online gaming motivation, self-concept clarity and problematic online gaming. More specifically, the study investigated the mediating role of gaming motives between self-concept clarity and problematic online gaming. Data from 509 young adult (M = 23.14, SD = 4.66) video game players from Croatia were analyzed. Problematic online gaming was positively correlated with social, competition, coping, fantasy and escape motives for playing online video ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 54 publications
3
44
0
1
Order By: Relevance
“…According to Erikson's Theory of Psychosocial Development [46], adolescents will actively explore and establish their self-identity at the "Identity versus Role Confusion" stage while adults will seek to build up their social relationships at the "Intimacy versus Isolation" stage. These intrapersonal and interpersonal needs are often shown to motivate gaming behaviors, particularly the involvement in the massively multiplayer online role-playing games [47,48]. In their study with 179 Korean undergraduates, Kim and Kim [47] found that social motivations significantly predicted excessive Internet gaming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Erikson's Theory of Psychosocial Development [46], adolescents will actively explore and establish their self-identity at the "Identity versus Role Confusion" stage while adults will seek to build up their social relationships at the "Intimacy versus Isolation" stage. These intrapersonal and interpersonal needs are often shown to motivate gaming behaviors, particularly the involvement in the massively multiplayer online role-playing games [47,48]. In their study with 179 Korean undergraduates, Kim and Kim [47] found that social motivations significantly predicted excessive Internet gaming.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the study showed that participants who were more motivated to overcome loneliness, build real-life social network, or increase virtual social network, were more likely to engage in excessive Internet gaming. In another study with 509 young adults in Croatia, it was revealed that lower levels of self-concept were associated with higher levels of problematic Internet gaming [48]. As such, adolescents and adults may be more inclined than children to play virtual games to build their self-identity and social relationships or to compensate such unfulfilled needs in real life.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to video game consumption habits, it turned out that students who have never played or play moderately, have a greater academic self-concept . High use of screen devices can generate low levels of self-esteem, self-concept and poor academic performance, although it has been shown that high use of mobile phones is positively related to social self-concept (McKay, Sumnall, Cole and Percy, 2012;Šporčić and Glavak-Tkalić, 2018). Not abusing video games enables students to use their time to do homework, share it with their families and be physically active in their extracurricular activities.…”
Section: Discussionmentioning
confidence: 99%
“…This association takes weight due to social networks and the possibility of playing online with users from anywhere in the world. The feeling of being part of a group and establishing connections between a group of peers in the same, is derived to a second level, because more and more young people establish social ties through chats of the games themselves or the social networks associated to them, hence the need to play games or use social networks to feel socially fulfilled Ramírez-Granizo et al, 2020;Šporčić and Glavak-Tkalić, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance and dissociation coping have been identified as a risk factor for a variety type of addictions, including IGD (Bowditch et al, 2018;Schneider et al, 2017). More recently, research has found that using video games as a palliative coping mechanism explains the associations between IGD and different personality and psychological factors, including psychiatric distress (Ballabio et al, 2017;Király et al, 2015), self-concept clarity (Šporčić & Glavak-Tkalić, 2018), and Dark Tetrad personality traits (i.e.,…”
Section: Discussionmentioning
confidence: 99%